EBG Structured Metamaterial Inspired Wideband MIMO Antenna for Mutual Coupling Reduction - Patchala, Karunakar; Raja Rao, Y; Prasad, A M (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
In this article, metamaterial inspired wideband MIMO antenna using EBG (Electromagnetic Band Gap) structure is presented. Designed MIMO antenna geometry consists of two square shaped monopole radiators with defected ground structure for proper impedance matching. The proposed antenna is fabricated on 1.6 mm thick, low cost FR4 substrate of dielectric constant 4.4 possessing an overall size of 22mm×36mm. The antenna shows simulated and measured-10 dB impedance bandwidths and the EBG structure exhibits single stop band and suppresses E-plane coupling over these bands. Isolation better than -15 dB is achieved over the complete impedance bandwidth. Radiation efficiency and peak gain of the antenna varies from 72%-86% and 2.8 dB to 5.6 dB respectively. Envelope correlation coefficient, diversity gain and channel capacity loss document the antennas behaviour. The antenna was fabricated  and measured. Measurement validated the simulation and showed that the  designed antenna can be well applied in wideband MIMO systems.